The Representation of Personal Resilience in Ghea Indrawari's Song Terima Kasih Sudah Bertahan: A Semiotic Analysis - Naura Salsabila; Somadi Sosrohadi; Sukirnoa Sukirnoa; Sara Dwi Anjani (Hasanuddin University, 2025)
Terima Kasih Sudah Bertahan is a song by Ghea Indrawari that narrates an emotional journey and personal experiences in facing life’s challenges. This study aims to analyze the representation of personal resilience in the song through three aspects: commitment, control, and challenge, using Roland Barthes' semiotic approach. The research data includes verbal texts (song lyrics) and nonverbal texts (visuals from the music video) sourced from the YouTube channel HITS Records – Music Video Terima Kasih Sudah Bertahan. Data collection techniques involved listening, note-taking, and screenshot methods. The research employs a descriptive qualitative approach, focusing more on meaning-making than generalization. The findings reveal that the representation of personal resilience in this song is portrayed through a strong commitment to endure and not give up, effective self-control in facing difficulties, and challenges faced with courage and determination.